2017
DOI: 10.2174/1573408012666160727165940
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Potential Plant Compounds as Survivin Inhibitors and its Anti-Cancer Efficacy by Molecular Docking

Abstract: Background: Survivin, smallest Inhibitor of Apoptosis Protein (IAP) mediates apoptosis pathway and cell cycle is tumor specific and therapeutic target for cancer research. Breast cancer is a dreadful disease with greater mortality rate, commonly in women globally. Aim: This study was undertaken to investigate the effect of indigenous Plant drugs by in-silico determination of antagonist for Survivin protein that was up regulated in breast cancer. Materials and Methods: The 3D structure of Survivin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…C6 and C7 were reported for their cytotoxicity, anti-inflammatory, and antivirus activities (Ohmoto and Koike, 1988;Han et al, 2001;Chen et al, 2009b;Lee et al, 2009;Liu P. et al, 2019); their antibacterial activity is reported here for the first time. C8 showed anticancer, antimalarial, anti-inflammatory, antidiabetic, anti-plasmodium, antiprotozoal, antibacterial, antifungal, and antivirus activities (Lagoutte et al, 2008;Ross et al, 2008;Almeida et al, 2011;Arias et al, 2011;Cebrian-Torrejon et al, 2011;Agrawal et al, 2013;Rashed et al, 2013;Amanulla et al, 2017;Cho et al, 2018;Makong et al, 2019); it was active against S. aureus (of inhibition zone diameter of 6.1 mm), but no activity against E. coli was observed (Casciaro et al, 2019), which is the same as our result. C9 showed cytotoxicity against HepG2 and 3B cells, but there are no reports thus far about its antimicrobial activity.…”
Section: Bioactivity Discussion Of Kumu Compoundssupporting
confidence: 90%
“…C6 and C7 were reported for their cytotoxicity, anti-inflammatory, and antivirus activities (Ohmoto and Koike, 1988;Han et al, 2001;Chen et al, 2009b;Lee et al, 2009;Liu P. et al, 2019); their antibacterial activity is reported here for the first time. C8 showed anticancer, antimalarial, anti-inflammatory, antidiabetic, anti-plasmodium, antiprotozoal, antibacterial, antifungal, and antivirus activities (Lagoutte et al, 2008;Ross et al, 2008;Almeida et al, 2011;Arias et al, 2011;Cebrian-Torrejon et al, 2011;Agrawal et al, 2013;Rashed et al, 2013;Amanulla et al, 2017;Cho et al, 2018;Makong et al, 2019); it was active against S. aureus (of inhibition zone diameter of 6.1 mm), but no activity against E. coli was observed (Casciaro et al, 2019), which is the same as our result. C9 showed cytotoxicity against HepG2 and 3B cells, but there are no reports thus far about its antimicrobial activity.…”
Section: Bioactivity Discussion Of Kumu Compoundssupporting
confidence: 90%